2010
DOI: 10.1007/s10494-010-9258-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Velocity and Fluctuating Pressure in a Turbulent Wing-tip Vortex Using Triple Hot-film Sensor and Miniature Total Pressure Probe

Abstract: We have developed a probe-system for simultaneous measurement of three velocity components and pressure in turbulent flows. A miniature total pressure probe is placed adjacent to the sensors of a triple hot-film probe in order to achieve the spatial resolution which is equivalent to that of the triple hot-film probe itself. The instantaneous static pressure is calculated from measured velocity and total pressure by means of a newly developed processing method based on the Bernoulli equation for unsteady flows.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They also proposed some techniques to calibrate the frequency response of the pressure-measuring system. The similar techniques have been adopted in several experimental studies (Iida et al, 1999;Naka et al, 2006;Tsuji et al, 2007;Kawata et al, 2011;Terashima et al, 2012) and successful measurement results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed some techniques to calibrate the frequency response of the pressure-measuring system. The similar techniques have been adopted in several experimental studies (Iida et al, 1999;Naka et al, 2006;Tsuji et al, 2007;Kawata et al, 2011;Terashima et al, 2012) and successful measurement results have been reported.…”
Section: Introductionmentioning
confidence: 99%